E-Learning Security Requirements - Chavan, Meenal; Manjare, Poonam (International Journal of Computer Sciences and Engineering, 2015)
The security is very crucial in developing an e-learning system. Emerging standards for distance learning and education influence in a major way the development of e-learning systems. E-learning system must be secured against manipulation from the side of the students and also it protects user’s privacy. This paper presents a review of e-learning privacy and security requirements.It investigates the more popular e-learning standards to determine their provisions and limitations for privacy and security. The capabilities of a number of existing privacy enhancing technologies, including methods for network privacy, security management, and trust systems, are reviewed and assessed.